2014 : « Une diaspora forte - une Turquie forte » - Ségolène Débarre (Diasporas: Circulations, Migrations, Histoire)
In 2014, Turkish citizens were able to vote abroad for the first time. This paper aims to analyse the symbolic meaning of the date, as reflecting Turkey’s “new diaspora policy”. The word ‘diaspora’ was not common in Turkish before the early 2010s; the Presidency of Turks Abroad and Related Communities (YTB), a state agency created in 2010, has contributed to its institutionalization and spread in order to serve the political and geopolitical interests of Ankara.